PENDAMPINGAN PENGEMBANGAN KEMAMPUAN MITIGASI BENCANA BERBASIS RENDERFOREST BAGI GURU SEKOLAH DASAR DI DAERAH RAWAN BENCANA GUNUNG SINABUNG RELOKASI SIOSAR MEDAN - Masri Perangin Angin, Laurensia; Halimatussakdiah; Lumbantobing, Panniance; Nabila, Mutiara; Aulia Aprianti, Cindy; Abda’u Ansya, Yusron (JS (JURNAL SEKOLAH), 2025)
Abstract: The problems found at SDN 047175 Siosar, with a total of 35 teachers, indicate that the curriculum and teaching materials have not systematically integrated disaster mitigation content, teachers' ability to teach mitigation topics is still limited, and most teachers are not yet accustomed to using digital applications like Renderforest to create interactive learning media. This condition is further exacerbated by Siosar's disaster-prone geographical location and limited supporting infrastructure. To address these challenges, a disaster mitigation mentoring program was implemented, utilizing Renderforest as a digital medium for creating animations, videos, and educational presentations. The implementation method includes the preparation, execution, assessment, and evaluation stages. The results of the activity show a significant improvement in teachers' understanding, digital media utilization skills, and student engagement in disaster simulations and projects. In conclusion, this mentoring is effective in improving disaster literacy. The recommendations are directed toward sustainable mentoring and program replication in other disaster-prone schools.  Keyword: Reflects the contents of the article   Abstrak: Permasalahan yang ditemukan di SDN 047175 Siosar dengan jumlah 35 guru menunjukkan bahwa kurikulum dan bahan ajar belum mengintegrasikan secara sistematis materi mitigasi bencana, kemampuan guru dalam mengajarkan topik mitigasi masih terbatas, serta sebagian besar guru belum terbiasa menggunakan aplikasi digital seperti Renderforest untuk membuat media pembelajaran interaktif. Kondisi ini semakin diperburuk oleh letak geografis Siosar yang rawan bencana serta keterbatasan infrastruktur pendukung. Untuk menjawab tantangan tersebut, dilakukan program pendampingan mitigasi bencana dengan memanfaatkan Renderforest sebagai media digital untuk pembuatan animasi, video, dan presentasi edukatif. Metode pelaksanaan meliputi tahap persiapan, pelaksanaan, penilaian, dan evaluasi. Hasil kegiatan menunjukkan peningkatan signifikan dalam pemahaman guru, keterampilan pemanfaatan media digital, serta keterlibatan siswa dalam simulasi dan proyek kebencanaan. Kesimpulannya, pendampingan ini efektif meningkatkan literasi kebencanaan. Rekomendasi diarahkan pada pendampingan berkelanjutan dan replikasi program di sekolah rawan bencana lainnya. Kata Kunci: Disaster Mitigation, Renderforest, Elementary School Teachers, Siosar Relocation, Mount Sinabung